Saving Africa's tropical forests through energy transition: A randomized controlled trial in Tanzania - Yonas Alem; Remidius D. Ruhinduka (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
The production of charcoal to meet cooking needs of urban households is one of the main causes of deforestation and degradation of Africa's tropical forests, which offer significant carbon sequestration capacity to the global economy. In collaboration with a reputable local microfinance institution, we designed a randomised controlled trial in urban Tanzania and offered LPG stoves through subsidy and on credit to measure their impact on charcoal consumption and the corresponding reduction in deforestation. We also investigate the impact of the stoves on cooking time of women, who are the default cooks of the household. We find that, relative to households in the control group, adoption of LPG stoves reduced charcoal consumption by about 30% in the treatment group 15 months after the intervention. This corresponds to an average reduction in deforestation of 0.04 ha/household/year. However, providing subsidies for stove purchases resulted in a larger reduction in charcoal use (38%) than did providing access on credit (27%) with the corresponding likely reduction in deforestation by 0.05 and 0.03 ha/household/year respectively. A social cost-benefit analysis suggests that the cost of both programs is far below the benefits of the averted carbon dioxide CO2 due to possible reduction in deforestation. A carefully conducted controlled cooking test shows that cooking with LP gas is 50% cheaper than cooking with charcoal and it reduces cooking time by about 44% - welfare effects clearly indicating that LPG is cost-effective to the household as well. We highlight the importance of relaxing households' financial constraints and improving access to credit to encourage urban households to switch to cleaner energy sources and save the remaining forest resources of Africa. – – Die Herstellung von Holzkohle zur Deckung des Kochbedarfs städtischer Haushalte ist eine der Hauptursachen für die Abholzung der tropischen Wälder Afrikas, die der Weltwirtschaft eine bedeutende Kapazität zur Kohlenstoffbindung bieten. In Zusammenarbeit mit einer angesehenen lokalen Mikrofinanzinstitution entwarfen wir eine randomisierte, kontrollierte Studie im städtischen Tansania und boten LPG-Öfen als Subvention und auf Kredit an, um ihre Auswirkungen auf den Holzkohleverbrauch und die entsprechende Verringerung der Entwaldung zu messen. Wir untersuchen auch die Auswirkungen der Öfen auf die Kochzeit von Frauen, die üblicherweise im Haushalt für das Kochen zuständig sind. Wir stellen fest, dass im Vergleich zu den Haushalten in der Kontrollgruppe die Einführung von LPG-Öfen den Holzkohleverbrauch in der Behandlungsgruppe 15 Monate nach der Intervention um etwa 30% reduzierte. Dies entspricht einer durchschnittlichen Verringerung der Entwaldung von 0,04 ha/Haushalt/Jahr. Die Bereitstellung von Subventionen für den Kauf von Öfen führte jedoch zu einer stärkeren Verringerung des Holzkohleverbrauchs (38%) als die Bereitstellung von Krediten (27%) mit der entsprechenden wahrscheinlichen Verringerung der Entwaldung um 0,05 bzw. 0,03 ha/Haushalt/Jahr. Eine soziale Kosten-Nutzen-Analyse deutet darauf hin, dass die Kosten beider Programme weit unter dem Nutzen aufgrund der möglichen Reduzierung der Entwaldung liegen. Ein sorgfältig durchgeführter kontrollierter Kochtest zeigt, dass das Kochen mit LP-Gas um 50% billiger ist als das Kochen mit Holzkohle und die Kochzeit um etwa 44% verkürzt - Wohlfahrtseffekte, die deutlich zeigen, dass LPG auch für den Haushalt kostengünstig ist. Wir betonen, wie wichtig es ist, die finanziellen Zwänge der Haushalte zu lockern und den Zugang zu Krediten zu verbessern, um die städtischen Haushalte zu ermutigen, auf sauberere Energiequellen umzusteigen und die verbleibenden Waldressourcen Afrikas zu retten.
Keywords: G21; H31; O10; O13; Q23; Q51; 330; charcoal; deforestation; carbon dioxide; LPG stoves; liquidity constraint; credit